2020
DOI: 10.1007/s00425-020-03433-y
|View full text |Cite
|
Sign up to set email alerts
|

Wettability, water absorption and water storage in rosette leaves of the dragon tree (Dracaena draco L.)

Abstract: Main conclusion Leaf surfaces of Dracaena draco are wettable and can absorb water. The thick, basal leaf part could act as a water reservoir that changes in volume with plant hydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
(53 reference statements)
0
5
0
1
Order By: Relevance
“…The absorption and subsequent utilisation and/or accumulation of atmospheric water by aerial plant organs (chiefly leaves) have been reported specially for xerophytes, halophytes and species subjected to temporary drought (Stone et al, 1950;Munn e-Bosch et al, 1999;Limm et al, 2009;Eller et al, 2013;Wang et al, 2016;Jura-Morawiec and Marcinkiewicz, 2020). However, few more specific investigations evaluated the contribution of various foliar epidermal structures to the uptake of surface-deposited water, such as hydatodes (Martin and von Willert, 2000) and scales (Wang et al, 2016), but chiefly trichomes (Grammatikopoulos and Manetas, 1994;Papini et al, 2010;Fern andez et al, 2014a;Pina et al, 2016;Li et al, 2018a,b;Li et al, 2019;.…”
Section: Foliar Absorption Pathways For Water and Solutesmentioning
confidence: 99%
“…The absorption and subsequent utilisation and/or accumulation of atmospheric water by aerial plant organs (chiefly leaves) have been reported specially for xerophytes, halophytes and species subjected to temporary drought (Stone et al, 1950;Munn e-Bosch et al, 1999;Limm et al, 2009;Eller et al, 2013;Wang et al, 2016;Jura-Morawiec and Marcinkiewicz, 2020). However, few more specific investigations evaluated the contribution of various foliar epidermal structures to the uptake of surface-deposited water, such as hydatodes (Martin and von Willert, 2000) and scales (Wang et al, 2016), but chiefly trichomes (Grammatikopoulos and Manetas, 1994;Papini et al, 2010;Fern andez et al, 2014a;Pina et al, 2016;Li et al, 2018a,b;Li et al, 2019;.…”
Section: Foliar Absorption Pathways For Water and Solutesmentioning
confidence: 99%
“…The cost–benefit margin gives the species a chance for survival under water-deficit environmental conditions. Moreover, Jura-Morawiec and Marcinkiewicz ( 2020 ) and Jura-Morawiec et al ( 2021b ) showed that for a long-term drought, D. draco has developed traits and mechanisms that are visible at every level of the organization of its body.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of palisade mesophyll area in the transverse section of the lamina to total mesophyll area (palisade index) was determined as Spal/(Spal+Sspon+Swat), where Spal, Sspon, Swat were areas of palisade mesophyll cells, spongy mesophyll cells and water-storage tissue respectively. We defined waterstorage tissue (water-storing parenchyma, hydrenchyma) as living mesophyll cells with large vacuoles, which were fully or partially chlorophyll-free (Shields 1950;Willert et al 1992;Evert & Eichhorn 2006;Ogburn & Edwards 2010;Jura-Morawiec & Marcinkiewicz 2020;Heyduk 2021). The ratio of total mesophyll area to intercellular spaces area in the transverse section of the lamina (mesophyll density) was determined as (Sint+Spal+Sspon+Swat)/Sint, where Sint was the area of intercellular spaces and the other abbreviations were the same as in the previous equation.…”
Section: Leaf Measurementsmentioning
confidence: 99%